Chemistry - Jill K Robinson; Mcmurray, John E Fay, Robert C (Noida Pearson, 2022)
Robinson/McMurry/Fay$1 (Bs Chemistry, known for a concise and united author voice, conceptual focus, extensive worked examples, and thoroughly constructed connections between organic, biological, and general chemistry, highlights the application of chemistry to students$1 (Blives and careers. Lead author Jill Robinson strengthens the student orientation by creating more engaging, active learning opportunities for students and faculty. With the 8th Edition, Robinson draws upon her exceptional teaching skills to provide new interactive experiences that help identify and address students$1 (Bpreconceptions.s
Keywords: Chemistry